Involvement of Arabidopsis Multi-Copper Oxidase-Encoding LACCASE12 in Root-to-Shoot Iron Partitioning: A Novel Example of Copper-Iron Crosstalk - Bernal, María; Krämer, Ute (Frontiers in Plant Science, 2021)
Numerous central biological processes depend on the participation of the essential elements iron (Fe) or copper (Cu), including photosynthesis, respiration, cell wall remodeling and oxidative stress protection. Yet, both Fe and Cu metal cations can become toxic when accumulated in excess. Because of the potent ligand-binding and redox chemistries of these metals, there is a need for the tight and combined homeostatic control of their uptake and distribution. Several known examples pinpoint an inter-dependence of Fe and Cu homeostasis in eukaryotes, mostly in green algae, yeast and mammals, but this is less well understood in multicellular plants to date. In Arabidopsis, Cu deficiency causes secondary Fe deficiency, and this is associated with reduced in vitro ferroxidase activity and decreased root-to-shoot Fe translocation. Here we summarize the current knowledge of the cross-talk between Cu and Fe homeostasis and present a partial characterization of LACCASE12 (LAC12) that encodes a member of the multicopper oxidase (MCO) protein family in Arabidopsis. LAC12 transcript levels increase under Fe deficiency. The phenotypic characterization of two mutants carrying T-DNA insertions suggests a role of LAC12 in root-to-shoot Fe partitioning and in maintaining growth on Fe-deficient substrates. A molecular understanding of the complex interactions between Fe and Cu will be important for combating Fe deficiency in crops and for advancing biofortification approaches.